Determinación de manchas de sangre no visibles mediante la técnica de luminol, en el laboratorio de química forense, de la Facultad de Ciencias Químicas y de la Salud, de la Universidad Técnica de Machala - Niola Camacho, Carolina M. (2012)
The present research shows that it clearly identifies the Luminol reagent spotting at first glance are not observed by the human eye, by its luminescence, which we clearly details the dark spot.